Los retos metodológicos en la exploración de violencias a personas trans privadas de libertad en el sistema penitenciario de Ecuador: caso Helen Maldonado (Tema Central) - Cuji Sigüenza, Annie (2025)
During the period 2021-2023, Ecuador experienced one of the worst prison crises. It was a time marked by serious structural problems due to an inadequate prison policy, which led to overcrowding and produced an escalation of violence never seen before that resulted in multiple prison massacres. This article aims to make visible the situation of violence suffered in prison contexts by trans women deprived of liberty who are placed in male wards without considering their gender identity. In addition, alternatives are explored to achieve comprehensive reparation in these complex cases, as well as to raise the methodological challenges represented by investigating issues of serious violations of human rights. To do this, the case of Helen Maldonado will be studied, a trans woman who in 2021 was held in the male ward of one of the mega-prisons built in Ecuador, called Penitenciaría del Litoral, where she was murdered during a riot. The dichotomous penitentiary construction deepens the problems of these historically discriminated groups, causing the failure to observe their intersectionality and preventing them from exploring forms of comprehensive reparation in cases of serious violations of their human rights. What is not spoken cannot be repaired